The Matching Concept - the Forgotten Accounting Principle? - Gos, Waldemar; Hońko , Stanisław (Studia Oeconomica Posnaniensia, 2016)
The principle of matching is associated with a paradox. IAS/IFRS, or Directive 2013/34 / EU, ignores this principle, which does not reduce its importance in the practice or teaching of accounting. This paradox has inspired the authors to present the importance of this principle in the era of the balance sheet approach to financial reporting, which has become a goal of the article. The last part of the text examines several financial reports with a view to exploring accruals, which are a direct consequence of the application of the matching concept.